AGROINDUSTRY BUSINESS DEVELOPMENT STRATEGY TEMPE SOYBEAN BY USING ANALYSIS SWOT ( CASE STUDY FOR 4 VILLAGE IN JEMBER REGENCY) - Ratih Rakhmawati; Edi Turjono (STIE Mandala Jember, 2017)
Tempe is one of the agroindustrial soy soybean processing in order to obtain value added by processingsoy dairy products. This study aims to determine: (1) Inventory soybean, (2) income agroindustrial tempe soybean, (3) efficiency tempe soybean costs agroindustrial production, (4) the value-added agro-industry tempe soybean, and (5) the development prospects of agro-industry tempe soybean , The method used is descriptive and analytical methods. Sampling method is purposive sampling method. The results of this study indicate that (1) agroindustry soybean tempeh has a total raw material costs were greater than the total cost of EOQ. (2) Income from soy milk agro-industry to scale house is 7,091,698.84 for small scale; USD 11,405,815.60 and US 11,622,766.70 to scale menengahindustri. (3) The cost of agro-industrial production of efficient soy milk. (4) the value-added agro-industry tempe soybean in various scales have been able to provide a positive values. (5) The results of a SWOT analysis of the agro-industry soybean tempeh in 4 villages Jember shows that the industry is in the white area (strengths - opportunities) that shows the industry has a prospect to be developed.